Diversity and Evolution of Type IV pili Systems in Archaea - Makarova, Kira S.; Koonin, Eugene V.; Albers, Sonja-Verena (Frontiers in Microbiology, 2016)
Many surface structures in archaea including various types of pili and the archaellum (archaeal flagellum) are homologous to bacterial type IV pili systems (T4P). The T4P consist of multiple proteins, often with poorly conserved sequences, complicating their identification in sequenced genomes. Here we report a comprehensive census of T4P encoded in archaeal genomes using sensitive methods for protein sequence comparison. This analysis confidently identifies as T4P components about 5000 archaeal gene products, 56% of which are currently annotated as hypothetical in public databases. Combining results of this analysis with a comprehensive comparison of genomic neighborhoods of the T4P, we present models of organization of 10 most abundant variants of archaeal T4P. In addition to the differentiation between major and minor pilins, these models include extra components, such as S-layer proteins, adhesins and other membrane and intracellular proteins. For most of these systems, dedicated major pilin families are identified including numerous stand alone major pilin genes of the PilA family. Evidence is presented that secretion ATPases of the T4P and cognate TadC proteins can interact with different pilin sets. Modular evolution of T4P results in combinatorial variability of these systems. Potential regulatory or modulating proteins for the T4P are identified including KaiC family ATPases, vWA domain-containing proteins and the associated MoxR/GvpN ATPase, TFIIB homologs and multiple unrelated transcription regulators some of which are associated specific T4P. Phylogenomic analysis suggests that at least one T4P system was present in the last common ancestor of the extant archaea. Multiple cases of horizontal transfer and lineage-specific duplication of T4P loci were detected. Generally, the T4P of the archaeal TACK superphylum are more diverse and evolve notably faster than those of euryarchaea. The abundance and enormous diversity of T4P in hyperthermophilic archaea present a major enigma. Apparently, fundamental aspects of the biology of hyperthermophiles remain to be elucidated.